Mechanical force regulation of YAP by F-actin and GPCR revealed by super-resolution imaging. Issue 4 (17th January 2020) - Gao, Jing; He, Lingli; Zhou, Lulu; Jing, Yingying; Wang, Feng; Shi, Yan; Cai, Mingjun; Sun, Jiayin; Xu, Haijiao; Jiang, Junguang; Zhang, Lei; Wang, Hongda
Abstract : Our work uncovers the role of GPCRs and F-actin in pressure-controlled YAP inactivation, and provides new insights into the mechanisms of mechanical regulation to the Hippo signaling pathway. Abstract : The Hippo signaling pathway plays critical roles in many biological processes including mechanotransduction. The key activator YAP of this pathway is considered as a central component of mechanotransduction signaling sensing the extracellular mechanical microenvironment changes, such as different cell density, the architecture of tissues and matrix stiffness. Although it has been largely studied that YAP is involved in these processes, the underlying mechanism of mechanical force-induced YAP regulation remains unclear. Here we exerted pressure on cell surfaces and investigated how YAP senses the extracellular mechanical force change using one of the super-resolution imaging techniques, dSTORM. We demonstrated that pressure promoted F-actin depolymerization, RhoA down-regulation, and LPAR1 (Gα12/13-coupled receptor) inactivation, which led to YAP cytoplasmic translocation and decreased clustering. Our work uncovers the role of GPCRs and F-actin in pressure-controlled YAP inactivation, and provides new insights into the mechanisms of mechanical regulation of the Hippo signaling pathway.